The relevance of historical studies and achievements of archipelago civilization progress: a study of sociological perspectives of Indonesian - Mursidi, Agus; Mahfud, Mahfud; Mubin, Dadang; Shomad, Abdul; Yudiana, I Kadek (Linguistics and Culture Review, 2021)
This historical study aims to see how history is relevant to the achievements of the progress of the civilization of the archipelago through the study of sociological science. For this reason, we have searched literature from several well-known journals. Next, we analyzed the literature to find data that could answer the questions of this study as much as possible. The data study starts with a coding system study and a specific evaluation to answer study questions with high validity elements. The journals we have visited include Google Books, Elsevier, Academic docs, and other publishers published ten years ago. Based on the discussion data, we can conclude that there is a very close relevance between the history of the Indonesian nation and the progress of civilization in the archipelago, which is now dominated by the influence of Islamic civilization and westernization. We hope this finding is helpful for future studies of Indonesian historical literature and civilization.